Influence of substrate design for in vitro mechanical testing - Dal Piva, Amanda-Maria-de Oliveira [UNESP]; Tribst, João-Paulo-Mendes [UNESP]; Borges, Alexandre-Luiz-Souto [UNESP]; de Melo, Renata-Marques [UNESP]; Bottino, Marco-Antonio [UNESP] (Medicina Oral, S.L., 2019)
Background: The goal of this study was to evaluate the influence of dental substrate simulator material, and the presence of root and periodontal ligament on the stress distribution in an adhesively-cemented monolithic crown. Material and Methods: Five (5) 3D models according to the substrate simulator material and shape were modeled with CAD software for conducting non-linear finite element analysis (FEA): Tooth with and without periodontal ligament - subgroup pl (groups Tooth+pl and Tooth-pl), machined tooth in epoxy-resin with and without pulp chamber - subgroup pc (ER+pc and ER-pc) and simplified epoxy-resin substrate without pulp chamber and roots (SiER). Next, adhesively-cemented monolithic crowns in zirconia reinforced lithium silicate were modeled over each substrate. The solids were then imported in STEP format to the analysis software and the contact between teeth and cylinder was considered perfectly bonded; whereas, the contacts involving the resin cement were considered as non-separated. The materials were considered isotropic, linearly elastic, and homogeneous. An axial load (600 N) was applied to the occlusal surface and results of maximum principal stress (MPa) on the restoration were required. Results: FEA revealed that all evaluated subtracts showed the crown intaglio surface as the most stressed region. The average stress and stress peaks were similar for restorations cemented onto Tooth+pl, Tooth-pl and ER+pc substrates, but, 13% higher in comparison to ER-pc and SiER substrates. Conclusions: Simplified substrates can be used to evaluate posterior full crown behavior without periodontal ligaments and roots, since the rigidity of the specimen is taken into account.
Keywords: Axial loading; Computed assisted numerical analisys; Finite element analysis; Methodological study; Monolithic crowns